2015
DOI: 10.1007/s12594-015-0217-4
|View full text |Cite
|
Sign up to set email alerts
|

Age Constraints of Udayagiri Domain of Nellore Schist Belt by Xenotime Dating around Pamuru, Prakasam District, Andhra Pradesh

Abstract: The Nellore Schist Belt (NSB) is a curvilinear Archaean schist belt, approximately 350 km long and 8-50 km wide. The Nellore Schist Belt is considered to be equivalent of the Sargur Group with a protolith age of 3.3-2.5Ga. Stratigraphically NSB is classified as the upper western Udayagiri Domain (dominated by metasediments) and lower eastern Vinjamuru Domain (dominated by metabasalts). Metabasalts of Vinjamuru Domain have been dated as of 2654 ± 100 Ma age, but so far no dates are available for the Udayagiri D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…The 1800-1900 Ma event identified Pb/ 206 Pb Age). in this study, combined with previously reported events from the Nellore schist belt (Vadlamani 2010;Vadlamani et al 2012;Das et al 2015), support another continental accretion event in the eastern part of the southern Indian craton as proposed by Saha et al (2015). The ∼1600 Ma event is considered to represent suturing of the Ongole domain with the Nellore schist belt (Bose et al 2011;Vijaya Kumar et al 2011;Henderson et al 2013) and this event is evident in sample EHV594 (figure 6).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The 1800-1900 Ma event identified Pb/ 206 Pb Age). in this study, combined with previously reported events from the Nellore schist belt (Vadlamani 2010;Vadlamani et al 2012;Das et al 2015), support another continental accretion event in the eastern part of the southern Indian craton as proposed by Saha et al (2015). The ∼1600 Ma event is considered to represent suturing of the Ongole domain with the Nellore schist belt (Bose et al 2011;Vijaya Kumar et al 2011;Henderson et al 2013) and this event is evident in sample EHV594 (figure 6).…”
Section: Discussionsupporting
confidence: 84%
“…Sample EHV594 also shows the 2400-2700 Ma age range, though not as pronounced as recorded in EHV591 (figure 6). The 1900 Ma age has also been reported previously in the Sm-Nd isochron age of the gabbro intrusions (Vadlamani 2010) and the 207 Pb/ 206 Pb zircon evaporation ages of andesitic rocks (Vadlamani et al 2012) in the Vinjamuru Group, and the U-Pb xenotime age from the Udaigiri Group (Das et al 2015). The KOC with an age range of 1850-1900Ma (Vadlamani 2010Vijaya Kumar et al 2010) is postulated to represent orogenic accretion that led to Columbia supercontinent assembly (Saha et al 2015).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…But age constraints on the amalgamation of the Kandra ophiolite belt within the NSB at 1900 Ma suggest that D1 cannot be older than this date. This is supported by a recent CHIME age from xenotime from within the Udaygiri Group of 1929 5 130 Ma (Das et al 2015), constraining the upper (older) limit of deformation/ metamorphism in the NSB. D2 deformation in the NFB-and possibly also in the NSB-occurred by 1590 Ma (Saha 2002;Dobmeier et al 2006;Saha et al 2010), as indicated by the ages of Vinukonda granite occurring at the western margin of the NSB and those of the syn-to late-tectonic Vellaturu granite that intrudes the NFB.…”
Section: Regional Deformationmentioning
confidence: 63%
“…The Udaygiri Group consists dominantly of metasedimentary rocks with minor intercalations of amygdaloidal/vesicular metabasalt in the lower part. The metasedimentary succession includes feldspathic grits, tuffaceous mudstones, and slates and cross-bedded quartzites, metamorphosed under low greenschist facies condition (Das et al 2015;Saha et al 2015).…”
Section: Geological Frameworkmentioning
confidence: 99%